Social Regulation of Negative Valence Systems During Development - Hu, Shannon; Packard, Katherine; Opendak, Maya (Frontiers in Systems Neuroscience, 2022)
Abstract The ability to sense, perceive, and respond appropriately to aversive cues is critical for survival. Conversely, dysfunction in any of these pathway components can lead to heightened avoidance of neutral or rewarding cues, such as social partners. The underlying circuitry mediating both negative valence processing and social behavior is particularly sensitive to early life experience, but mechanisms linking experience to pathology remain elusive. Previous research in humans, rodents, and non-human primates has highlighted the unique neurobiology of the developing infant and the role of the caregiver in mediating the infant’s negative valence circuitry, and the importance of this early social relationship for scaffolding lasting social behavior. In this review, we summarize current literature on the development of negative valence circuits in the infant and their social regulation by the caregiver following both typical and adversity-rearing. We focus on clinically-relevant research in infant rodents which highlights the amygdala and its interface with the mesolimbic dopamine system through innervation from the ventral tegmental area (VTA) as a locus of dysfunction following early life adversity. We then describe how these circuits are recruited to perturb life-long social behavior following adversity and propose additional therapeutic targets in these circuits with an eye toward developing age-appropriate interventions.